Mechanism of Embrittlement of Metals by Surface-Active Elements - Teus, S.M.; Shanina, B.D.; Konchits, A.A.; Mogilny, G.S.; Gavriljuk, V.G. (Металлофизика и новейшие технологии, 2018)
The nature of mechanical degradation of metals caused by surface-active elements is studied based on the effects of iodine and gallium in austenitic steels and using abinitio calculations and experimental measurements of electronic structure, X-ray diffraction, mechanical spectroscopy, and mechanical tests. A significant increase in the density of electron states at the Fermi level for iodine in f.c.c. iron is shown that is in consistent with the measurements of the increased concentration of free electrons caused by iodine in austenitic steels. Consequently, the increase in mobility of dislocations by iodine and gallium in austenitic steels is revealed. The localization of the enhanced plastic deformation is discussed as a condition for brittleness. The obtained results are at variance with the widely spread opinion about the determining role of surface energy in a liquid-metal brittleness and, instead, are interpreted based on the correlation between atomic interactions and dislocation properties. Applicability of the available HELP and AIDE hypotheses is discussed. Природа механической деградации металлов, обусловленной поверхностно-активными элементами, была изучена, основываясь на влиянии йода и галлия на аустенитные стали и используя abinitio-расчёты и экспериментальные исследования электронной структуры, рентгеновскую дифракцию, механическую спектроскопию и механические испытания. Показано существенное повышение плотности электронных состояний на уровне Ферми в случае йода в ГЦК-железе, что согласуется с измерениями, в которых была зафиксирована повышенная концентрация свободных электронов, вызванная йодом в аустенитных сталях. Как следствие, установлено повышение мобильности дислокаций, вызванное йодом и галлием в аустенитных сталях. Обсуждается роль локализации повышенной пластической деформации в качестве условия хрупкости. Полученные результаты противоречат широко распространённому мнению об определяющей роли поверхностной энергии в жидкометаллической хрупкости и, вместо этого, интерпретируются, основываясь на корреляции между атомными взаимодействиями и дислокационными свойствами. Обсуждается применимость гипотез HELP и AIDE. Природу механічної деґрадації металів, яку спричинено дією поверхнево-активних елементів, було досліджено, виходячи із впливу Йоду та Ґалію на аустенітні сталі та використовуючи abinitio-розрахунки й експериментальні дослідження електронної структури, рентґенівську дифракцію, механічну спектроскопію та механічні випробування. Показано істотне підвищення густини електронних станів на рівні Фермі у випадку Йоду в ГЦК-залізі, що узгоджується з вимірюваннями, в яких було зафіксовано підвищену концентрацію вільних електронів, яку спричинено Йодом в аустенітних сталях. Як наслідок, встановлено підвищення мобільности дислокацій, спричинене Йодом і Ґалієм в аустенітних сталях. Обговорюється роль локалізації підвищеної пластичної деформації в якості умови крихкости. Одержані результати суперечать розповсюдженим твердженням про визначальну роль поверхневої енергії в рідкометалевому окрихченні і замість цього інтерпретуються, виходячи з кореляції між атомними взаємодіями та дислокаційними властивостями. Обговорюється коректність гіпотез HELP та AIDE.